Synthesis of Functionalized Pseudopeptides through Five-Component Sequential Ugi/Nucleophilic Reaction of N-Substituted 2-Alkynamides with Hydrazides - Maghari, Shokoofeh; Ramezanpour, Sorour; Balalaie, Saeed; Darvish, Fatemeh; Rominger, Frank; Bijanzadeh, Hamid Reza (The journal of organic chemistry, 2013)
Five-component sequential Ugi/nucleophilic addition reaction of aromatic aldehydes, primary amines, propiolic acid, isocyanides, and hydrazides has been developed in order to access polyfunctional pseudopeptides. The reaction may proceed through formation of N-substituted 2-alkynamides as intermediates. This process is found to be mild and operationally simple with broad substrate scope.
Gesehen am 11.06.2021